The sole fact of pure reason Kant's quasi-ontological argument for the categorical imperative - Beyleveld, Deryck (Kantstudien. Ergänzungshefte ;, 2020)
This book presents a comprehensive analysis of Kant's justification of the categorical imperative. The book contests the standard interpretation of Kant's views by arguing that he never abandoned his view about this as expressed in his Groundwork. It is distinctive in the way in which it places Kant's argument in the context of his transcendental philosophy as a whole, which is essential to understand it as an argument from within human agential self-understanding. The book reviews that existing literature, then presents a logical construction of Kant's argument, which it defends by examining what Kant has to say about synthetic a priori practical propositions in the context of his transcendental philosophy as a whole, and by a detailed examination of how he presents his argument in the Second Critique and the Groundwork. Particular attention is given to the views of two scholars who share many of the views expressed in this book: Klaus Steigleder and Michael Wolff. Special attention is also given to the views of Owen Ware, who, while sharing many of our arguments has a very different overall view. The concluding chapter provides a statement about the validity of Kant's argument.